Geriatric care: ways and means of providing comfort - Patricia Cruz Pontifice Sousa Valente Ribeiro; Rita Margarida Dourado Marques; Marta Pontifice Ribeiro
ABSTRACT Objective: To know the ways and means of comfort perceived by the older adults hospitalized in a medical service. Method: Ethnographic study with a qualitative approach. We conducted semi-structured interviews with 22 older adults and participant observation of care situations. Results: The ways and means of providing comfort are centered on strategies for promoting care mobilized by nurses and recognized by patients(clarifying/informing, positive interaction/communication, music therapy, touch, smile, unconditional presence, empathy/proximity relationship, integrating the older adult or the family as partner in the care, relief of discomfort through massage/mobilization/therapy) and on particular moments of comfort (the first contact, the moment of personal hygiene, and the visit of the family), which constitute the foundation of care/comfort. Final considerations: Geriatric care is built on the relationship that is established and complete with meaning, and is based on the meeting/interaction between the actors under the influence of the context in which they are inserted. The different ways and means of providing comfort aim to facilitate/increase care, relieve discomfort and/or invest in potential comfort.